Low Price Equilibrium in Multi-Unit Auctions: The GSM Spectrum Auction in Germany - Veronika Grimm; Frank Riedel; Elmar G. Wolfstetter (Center for Economic Studies and ifo Institute (CESifo), 2001)
The second-generation GSM spectrum auction in Germany is probably the most clear cut example of a low price outcome in a simultaneous ascending-bid auction.The present paper gives an account of the events, describes the auction rules and market conditions, and provides a theoretical explanation of low price equilibria in simultaneous, ascending-bid auctions.In particular it is shown that the low price equilibrium that implements the efficient allocation is the unique perfect equilibrium of that game.
Keywords: 330; Multi-unit auctions; spectrum auctions; telecomm-unications; industrial organization; game theory